Promoting Ocean Literacy in Elementary School Students Through Investigation Activities and Citizen Science - Boaventura, Diana; Neves, Ana Teresa; Santos, Jaime; Pereira, Paula Colares; Luís, Cristina; Monteiro, António; Cartaxana, Alexandra; Hawkins, Stephen John; Caldeira, Maria Filomena; Ponces de Carvalho, António (Frontiers in Marine Science, 2021)
To enable the process of energy transition towards carbon neutrality, it is important to educate the community on the need for social, economic, environmental and institutional transformation, and to educate and inform citizens to participate proactively in this change. This study evaluated the effectiveness of participation by elementary school students in educational activities and citizen science actions in enhancing their scientific knowledge and skills related to Ocean Literacy in the context of climate change. The activities were directed to children (aged 9–11) and involved pre-service teachers, in-service teachers and researchers, in formal and non-formal contexts. A total of 329 elementary school students participated in interdisciplinary science activities, focusing on the cause & effect of climate change in the ocean. They learned to identify rocky shore marine species used to monitor climate change and acquired ICT skills by inserting species observations in a biodiversity mapping platform. Finally, students worked collaboratively to communicate to the community what they have learned through an exhibition at the Museum João de Deus. To assess the impact of the activities on acquisition of scientific knowledge and skills by the students, a mixed methodology was applied using pre and post-tests, analysis of the data inserted by students in the platform, and content analysis of the students’ work for the museum exhibition. The results of pre and post-tests revealed a significant increase in knowledge of the effects of climate change on the rocky shore species distribution, as well as of the importance of monitoring these species distribution. The data from the online biodiversity platform showed that 42% of the species identifications made by the students were correct. The ability of the students to communicate their learning to the wider community was evaluated by the scientific content, structure, presentation and creativity and of posters, models, videos and games produced. Most of students focused their communications and creations on the greenhouse effect, cause & effect of climate change in the ocean and biodiversity. This study reinforces the importance of addressing Ocean Literacy and climate change through formal and non-formal educational activities with an investigative nature.